Assessment of the water quality of the Lurín river, Lima, Perú, using biotic indices during the high-flow season - Zurita Castillo, Julio Alberto (2025)
The water quality of the Lurín River, Lima, Peru, shows evidence of deterioration due to urban growth and the discharge of domestic and industrial effluents, which affect the ecological integrity of its lower basin. In this context, the present study aimed to evaluate water quality during the high-flow season using biotic indices based on benthic macroinvertebrates (BMI) as a complementary tool to conventional physicochemical and microbiological parameters. Six sampling stations were established along 5 km of the river channel, where macroinvertebrates were collected manually and with a Surber net (500 µm mesh), following a standardized protocol at each point. In the field, temperature, pH, electrical conductivity (EC), and dissolved oxygen (DO) were measured, and in the laboratory, thermotolerant coliforms (TTC) and Escherichia coli (Castellani & Chalmers, 1919) were analyzed. Organisms were identified to the family level, and the BMWP/Col, ASPT, ChIBF, and %EPT indices were calculated. In addition, Pearson correlation analyses, the Morisita–Horn similarity index, and the non-parametric Friedman test were applied to compare the indices. A total of 1479 individuals belonging to 11 families were identified, with Leptohyphidae, Hydropsychidae, and Simuliidae being the most abundant. The BMWP/Col, ASPT, and ChIBF indices exhibited consistent patterns, whereas %EPT differed significantly according to the Friedman test. The evaluated stations complied with the Peruvian ECA–water standards for EC, pH, and DO, but not for TTC, and only E1 remained within the permitted limit for E. coli. The Morisita–Horn index revealed high similarity (>95%) among stations E1–E4 and E2–E5 relative to E3 and E6. Consistently, these two stations concentrated the lowest scores: E3 obtained the lowest classification according to the %EPT index, while E6 recorded minimum values in BMWP/Col, ASPT, and ChIBF. Overall, the results demonstrate that biotic indices constitute an effective and complementary tool for the ecological assessment of water quality in the lower Lurín River basin during high-flow periods.